Analisis Komparasi Daya Tarik Kerja Antara Generasi Y dan Generasi Z pada Mahasiswa Manajemen Fakultas Ekonomi dan Bisnis Universitas Riau : Comparative Analysis of Employer Attractiviness Between Generation Y and Generation Z in Management Students of the Faculty of Economics and Business Riau University - Garnasih, Raden Lestari; Roesdi, Rosnelly; Maulidia, Nurul (MUI Kota Pekanbaru, 2024)
The purpose of this study was to compare the attractiveness of work between Generation Y and Generation Z in Management students of the Faculty of Economics and Business, Riau University. This research was conducted on undergraduate and postgraduate students with a population of 436 people. the sampling technique used was non-probability sampling method, namely purposive sampling (136 Management students of the Faculty of Economics and Business, Riau University).The data collection method is a questionnaire. The results showed that: 1) there are differences in interest value, social value, economic value and development value of employer attractiviness and there are no differences in application value between Generation Y and Generation Z in Management students of the Faculty of Economics and Business, Riau University. 2) The most attractive dimension for Generation Y is economic value and for Generation Z is social value.